(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The Department of Anesthesiology and Intensive Care is one of the most complex and responsible structural units of a medical institution. The effectiveness of this department largely depends on the proper organization of nursing activities, quality control of medical care, and rational allocation of resources. This article examines the role of the head nurse in organizing the work of the Department of Anesthesiology and Intensive Care, her main functions, responsibilities, and significance in ensuring patient safety and the efficiency of the treatment process. It is shown that competent management of nursing staff, compliance with sanitary and epidemiological requirements, and control of medical equipment are important factors in improving the quality of intensive care.